2013
DOI: 10.3390/toxins5071314
|View full text |Cite
|
Sign up to set email alerts
|

Short Toxin-like Proteins Attack the Defense Line of Innate Immunity

Abstract: ClanTox (classifier of animal toxins) was developed for identifying toxin-like candidates from complete proteomes. Searching mammalian proteomes for short toxin-like proteins (coined TOLIPs) revealed a number of overlooked secreted short proteins with an abundance of cysteines throughout their sequences. We applied bioinformatics and data-mining methods to infer the function of several top predicted candidates. We focused on cysteine-rich peptides that adopt the fold of the three-finger proteins (TFPs). We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The uPAR signaling is responsible for initiating invasion and metastasis via the activation of the plasminogen activator/plasmin cascade in breast cancers and play a role in stimulating the RAS/ERK pathway to control invasion in cancer cells [ 148 ]. The LU domain has been predicted to play a role in cancer diagnosis and malfunction of immune system [ 149 ]. It is plausible that all Ly6 family of genes may have common mechanism in tumorigenesis and their role in poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The uPAR signaling is responsible for initiating invasion and metastasis via the activation of the plasminogen activator/plasmin cascade in breast cancers and play a role in stimulating the RAS/ERK pathway to control invasion in cancer cells [ 148 ]. The LU domain has been predicted to play a role in cancer diagnosis and malfunction of immune system [ 149 ]. It is plausible that all Ly6 family of genes may have common mechanism in tumorigenesis and their role in poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Ly6 proteins is underscored by their implication in diseases such as Mal de Meleda [ 21 – 23 ]; in nervous system functions such as synaptic transmission, visual plasticity, anxiety, and sleep [ 7 , 14 , 24 , 25 ]; and in immune and stem cell functions [ 16 , 23 , 26 32 ]. In some of these cases individual Ly6 proteins have been shown to exert their effects through antagonism of nAChRs, but the mechanisms underlying these effects and the structural motifs that are involved have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…ClanTox is species independent, as opposed to ConoDictor and ConoSorter, and can be used to identify toxin-like sequences. For example, ClanTox was used to discover toxin-like proteins in mammalian transcriptomes [ 79 ], and some of the identified peptides are modulators of cell signaling acting at nicotinic acetylcholine receptors using a three-finger snake toxin fold [ 80 , 81 ]. On the basis of convergent evolution of toxins in different phila, Starcevic et al identified sequences motifs that seem to be specifically used by toxins [ 82 ].…”
Section: Discovery Of Toxins From Venom Gland Transcriptomesmentioning
confidence: 99%